How Can Earth Scientists Contribute to Community Resilience? Challenges and Recommendations - Virapongse, Arika; Gupta, Rupanwita; Robbins, Zachary J.; Blythe, Jonathan; Duerr, Ruth E.; Gregg, Christine (Frontiers in Climate, 2022)
Community resilience increases a place-based community’s capacity to respond and adapt to life-changing environmental dynamics like climate change and natural disasters. In this paper, we aim to support Earth science’s understanding of the challenges communities face when applying Earth science data to their resilience efforts. First, we highlight the relevance of Earth science in community resilience. Then, we summarize these challenges of applying Earth science data to community resilience: Inequity in the scientific process; Gaps in data ethics and governance; A mismatch of scale and focus; and Lack of actionable information for communities. Lastly, we offer the following recommendations to Earth science as starting points to address the challenges presented: Integrate community into the scientific data pathway; Build capacity to bridge science and place-based community needs; Reconcile openness with self-governance; and Improve access to data tools to support community resilience.